Spectophotometric intracutaneous analysis: an investigation on photodamaged skin of immunocompromised patients. (13th October 2014) - Stimpfle, D.W.; Serra, A.L.; Wüthrich, R.P.; French, L.E.; Braun, R.P.; Hofbauer, G.F.L.
Abstract Background SIAscopy (Spectrophotometric Intracutaneous Analysis) enables non‐invasive analysis of the skin. Objective We wanted to determine whether SIAscopy is able to detect and differentiate the skin chromophores melanin, collagen and haemoglobin and the influence of immunosuppressive drugs and other known risk factors for non‐melanoma skin cancer (NMSC). Methods Volunteers and patients were measured by SIAscopy at six spots on sun‐exposed and two spots on sun‐protected skin. Measurements were transformed by SIAmetrics into arbitrary units and statistically analysed. Results Melanin was shown to be higher with age (+1.73759 a.u.; P < 0.0001), sun exposure (+47.03998 a.u.; P < 0.0001), immunosuppression (+10.48526 a.u.; P < 0.0001) and lower in males (−26.50952 a.u.; P < 0.0001). Collagen was lower with increasing age (−0.29162 a.u.; P < 0.0001) and sun exposure (−6.85586 a.u.; P < 0.0001) but higher with male sex (+8.34251 a.u.; P < 0.0001) and immunosuppression (+5.79171 a.u.; P = 0.0001). Haemoglobin was lower with increasing age (−0.23833 a.u.; P = 0.0005), but higher with male sex (+18.51976 a.u.; P < 0.0001) and sun exposure (+13.74523 a.u.; P < 0.0001). Haemoglobin content was not associated to immunosuppression. Conclusion Our results encourage the use of SIAscopy as a tool to better gauge an individual patient's NMSC risk factors. Further studies should help to better delineate SIAscopy as a prognostic tool.